2001
DOI: 10.1542/peds.108.6.e110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Resuscitation Skills in New Residents Before and After Pediatric Advanced Life Support Course

Abstract: ABSTRACT. Objective. Acquisition of resuscitation skills taught in advanced resuscitation courses has not been evaluated. We sought to determine the interobserver reliability of a resuscitation performance skills checklist to assess resident performance of bag mask ventilation, intubation, defibrillation, and intraosseous vascular access, and to measure skill acquisition by entering residents after a pediatric advanced life support (PALS) course.Design. The resuscitation skills of all 39 pediatric R1's in 2 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 11 publications
2
37
2
5
Order By: Relevance
“…Many pediatric and adult studies have demonstrated the effectiveness of resuscitation training courses, but retention of knowledge and skills appears to be a problem. [2][3][4][5] Despite completion of these courses, trainees experience significant stress in real-life situations as they feel unprepared to deal with such clinical emergencies. [5][6][7] Increasing trainee numbers, decreasing training hours and an overall impetus to shorten training curriculum have all contributed to an overall reduction in clinical exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Many pediatric and adult studies have demonstrated the effectiveness of resuscitation training courses, but retention of knowledge and skills appears to be a problem. [2][3][4][5] Despite completion of these courses, trainees experience significant stress in real-life situations as they feel unprepared to deal with such clinical emergencies. [5][6][7] Increasing trainee numbers, decreasing training hours and an overall impetus to shorten training curriculum have all contributed to an overall reduction in clinical exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Adult and paediatric LSCs can lead to an immediate increase in both theoretical knowledge and practical skills. 18,19 Unfortunately, this is often shortlived and performance can deteriorate alarmingly. 20 For these reasons evaluation of LSCs at the level of learning should focus not on the immediate learning effect but on long-term retention.…”
Section: Resultsmentioning
confidence: 99%
“…31 Quan et al suggest that the early recognition of potentially life-threatening situations would be an appropriate measure, although this would be difficult to operationalize. 18 Outcome is also heavily influenced by severity of illness -particularly in a heterogenous disease like trauma -and stratification systems for the severity of injury are controversial. The degree of improvement expected from an LSC will depend on the level of care before training, with the greatest improvements expected where this is lowest.…”
Section: Resultsmentioning
confidence: 99%
“…6 Waarschijnlijk spelen methodologische factoren hierbij een belangrijke rol. Omdat het volgen van een reanimatiecursus aan het begin van de opleiding een aangetoond positief effect heeft op het aanleren van reanimatievaardigheden, 7 is aan te bevelen om de aios kindergeneeskunde aan het begin van hun opleiding een reanimatiecursus, bijvoorbeeld de NLS, te laten volgen voordat zij zelf in de dagelijkse praktijk pasgeborenen gaan opvangen. Hierbij moet wel de kanttekening geplaatst worden dat deze cursussen alleen effectief zijn en blijven indien regelmatig, minimaal iedere zes maanden, herhaling en bijscholing plaatsvindt.…”
Section: Discussieunclassified